Spectral dimension on spatial hypersurfaces in causal set quantum gravity - Eichhorn, Astrid; Surya, Sumati; Versteegen, Fleur (Classical and quantum gravity, 2019)
An important probe of quantum geometry is its spectral dimension, defined via a spatial diffusion process. In this work we study the spectral dimension of a ‘spatial hypersurface’ in a manifoldlike causal set using the induced spatial distance function. In previous work, the diffusion was taken on the full causal set, where the nearest neighbours are unbounded in number. The resulting super-diffusion leads to an increase in the spectral dimension at short diffusion times, in contrast to other approaches to quantum gravity. In the current work, by using a temporal localisation in the causal set, the number of nearest spatial neighbours is rendered finite. Using numerical simulations of causal sets obtained from d = 3 Minkowski spacetime, we find that for a flat spatial hypersurface, the spectral dimension agrees with the Hausdorff dimension at intermediate scales, but shows clear indications of dimensional reduction at small scales, i.e. in the ultraviolet. The latter is a direct consequence of ‘discrete asymptotic silence’ at small scales in causal sets.